2017
DOI: 10.4103/ijc.ijc_87_17
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: Experience of an institute in limited resource setting

Abstract: Proteasome inhibitors significantly improved the median survival for patients with MM (ISS II and ISS III) treated in a limited resource setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
3
8
2
Order By: Relevance
“…In our study, patients received VAD (vincristine, adriamycine, dexamethason) regimen for six cycles and thalidomide for maintenance therapy. It was similar to the study that was reported by Jacob et al [ 14 ] with result of median survival for the ISS stage I, ISS stage II, and ISS stage III groups was 48 months, 21 and 27 months respectively and it was also lower than our study. If our study was compared to the Western data, where the 5-year survival post-transplant ASCT for ISS I, ISS II, and ISS III was 82%, 62%, and 40%, respectively [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, patients received VAD (vincristine, adriamycine, dexamethason) regimen for six cycles and thalidomide for maintenance therapy. It was similar to the study that was reported by Jacob et al [ 14 ] with result of median survival for the ISS stage I, ISS stage II, and ISS stage III groups was 48 months, 21 and 27 months respectively and it was also lower than our study. If our study was compared to the Western data, where the 5-year survival post-transplant ASCT for ISS I, ISS II, and ISS III was 82%, 62%, and 40%, respectively [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…Multiple myeloma has a male predominance [ 13 ], with median age 54 years (range 39–85) [ 14 ]; with the most common presenting symptoms were pain, impending/pathological fracture, anemia, and neurological deficit [ 6 ]. It is consistent with our study which showed that 18 male and 14 female with median age was 59 years (range 43–79).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 49 (41.88%) patients were staged ISS-III which was more compared to other Indian study by Jacob LA et al (2017) and western studies by Greipp PR et al (2005) and Attal M et al (2015) where frequency of ISS-III was 39%, 39% and 18% respectively (21,6,22).…”
Section: Discussioncontrasting
confidence: 51%
“…Estimated OS in our study (Fig 2 A) was higher than those reported in other studies (western and Indian) as illustrated in Table 2 . 14 , 16 , 18 , 21 , 23 , 24 The higher OS in our study can be attributed to a better hospital network, pan-India referral system, and fully sponsored therapy with no cost to the patient and better living standards of our clientele.…”
Section: Discussionmentioning
confidence: 64%